Epicardial fat thickness is associated with impaired coronary flow reserve in hemodialysis patients - AŞICIOĞLU, EBRU (WILEY, 2014)
Cardiovascular disease (CVD) is the main cause of mortality in hemodialysis (HD) patients. Epicardial fat tissue (EFT) is a new risk factor in CVD. The aim of this study was to evaluate the association between EFT and coronary artery flow reserve (CFR), which is an early indicator of endothelial dysfunction in coronary vessels of HD patients. We performed a cross-sectional study including 71 chronic HD patients and 65 age- and sex-matched healthy controls. Epicardial fat tissue was significantly higher in HD patients when compared to healthy controls (6.53 +/- 1.01 mm vs. 5.79 +/- 1.06 mm, respectively, P < 0.001). On transthoracic Doppler echocardiography, CFR values were significantly lower in HD patients when compared to healthy controls (1.73 +/- 0.11 vs. 2.32 +/- 0.28, P < 0.001). Correlation analysis showed CFR values to be inversely correlated with EFT (r = -0.287, P < 0.05). Multiple linear regression analysis was used to define independent determinants of EFT in HD patients. Artery flow reserve, age, body mass index and total cholesterol levels were independently correlated with EFT thickness. This study demonstrated that EFT was significantly higher among HD patients compared to healthy controls. In addition, this study was the first to demonstrate an inverse correlation between EFT and CFR in this patient population.
Keywords: hemodialysis; atherosclerosis; epicardial fat tissue; Coronary flow reserve; ADIPOSE-TISSUE; VELOCITY RESERVE; RISK-FACTORS; DISEASE; ADIPOCYTOKINES; DYSFUNCTION; DISORDERS